(untitled) (Journal of Dhaka Medical College, 2015)
Immunoglobulin M nephropathy (IgMN) is an idiopathic glomerulonephritis characterized by a variable degree of mesangialhypercellularity and diffuse IgM deposits.Patients usually presents with refractory nephrotic syndrome (NS) and hematuria. We present two patients with IgM nephropathy one with frequently relapsing NS with steroid dependence, treated with oral steroid and cyclophosphamide subsequently with tacrolimus. The patient showed complete remission but breakthrough relapses occurredduring the course of steroid treatment.The second case presented with persistentgross hematuria and nephroticrange proteinuria for 6 months. The patient showed complete remission of proteinuria and hematuria with oral steroid andremained on remission for9 months. Then again developed hematuria & proteinuria and subsequently showed response to oral steroid and cyclphosphamide . Renal histopathology & immunofluorescence study of first case revealed normal mesangial cellularity and basement membrane thickness with mesangial deposits of IgM. Second case showed global mesangial proliferation with increasing mesangial matrix with moderate mesangial deposits of IgM. DOI: http://dx.doi.org/10.3329/jdmc.v23i1.22709 J Dhaka Medical College, Vol. 23, No.1, April, 2014, Page 131-133